Упростите выражения: а)(√6+√3)√12-2√6*√3
б)(√10+√5)√20-5√8
а)
б)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
а)![(\sqrt{6}+\sqrt{3})*\sqrt{12}-2*\sqrt{6}*\sqrt{3}= \sqrt{6}*\sqrt{12}+6-2*\sqrt{6}*\sqrt{3}=6 (\sqrt{6}+\sqrt{3})*\sqrt{12}-2*\sqrt{6}*\sqrt{3}= \sqrt{6}*\sqrt{12}+6-2*\sqrt{6}*\sqrt{3}=6](https://tex.z-dn.net/?f=%28%5Csqrt%7B6%7D%2B%5Csqrt%7B3%7D%29%2A%5Csqrt%7B12%7D-2%2A%5Csqrt%7B6%7D%2A%5Csqrt%7B3%7D%3D%20%5Csqrt%7B6%7D%2A%5Csqrt%7B12%7D%2B6-2%2A%5Csqrt%7B6%7D%2A%5Csqrt%7B3%7D%3D6)
б)![(\sqrt{10}+\sqrt{5})*\sqrt{20}-5*\sqrt{8}=\sqrt{10}*\sqrt{20}+\sqrt{5}*\sqrt{20}-5*\sqrt{8}=10 (\sqrt{10}+\sqrt{5})*\sqrt{20}-5*\sqrt{8}=\sqrt{10}*\sqrt{20}+\sqrt{5}*\sqrt{20}-5*\sqrt{8}=10](https://tex.z-dn.net/?f=%28%5Csqrt%7B10%7D%2B%5Csqrt%7B5%7D%29%2A%5Csqrt%7B20%7D-5%2A%5Csqrt%7B8%7D%3D%5Csqrt%7B10%7D%2A%5Csqrt%7B20%7D%2B%5Csqrt%7B5%7D%2A%5Csqrt%7B20%7D-5%2A%5Csqrt%7B8%7D%3D10)